1997
DOI: 10.1111/j.1600-0609.1997.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal CD8+ and CD52 T cells are induced in responding B cell lymphoma patients treated with Campath‐1H* (anti‐CD52)

Abstract: Five patients with non‐Hodgkin's lymphoma (NHL) and 4 patients with chronic lymphocytic leukaemia (CLL) were treated with the CDR‐grafted (rat × human) monoclonal antibody (mAb) Campath‐1H (anti‐CD52). Tumour regression was noted preferentially in peripheral blood and in the bone marrow but lymph nodes were less affected. Normal blood B and T cells were profoundly reduced in all patients whereas CD16+ NK cells and CD14+ monocytes decreased marginally. In all responding CLL patients CD52‐negative T but not B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Alemtuzumab is a known T cell, B cell and dendritic cell depleting antibody [37], [38]. Alemtuzumab has been previously reported to spare NK cells [39], marginally decrease CD16 + NK cell counts until 1–2 months after treatment [40], [41], or to deeply suppress NK cells for over 9 months after treatment [42]. Our results demonstrate that compared to other lymphocytes, NK cells are relatively spared by alemtuzumab.…”
Section: Discussionmentioning
confidence: 54%
“…Alemtuzumab is a known T cell, B cell and dendritic cell depleting antibody [37], [38]. Alemtuzumab has been previously reported to spare NK cells [39], marginally decrease CD16 + NK cell counts until 1–2 months after treatment [40], [41], or to deeply suppress NK cells for over 9 months after treatment [42]. Our results demonstrate that compared to other lymphocytes, NK cells are relatively spared by alemtuzumab.…”
Section: Discussionmentioning
confidence: 54%
“…Alemtuzumab has been approved for the treatment of patients with advanced chronic lymphocytic leukemia (CLL) [6], [7], [8]. This antibody has also been utilized in the treatment of a wide range of diseases including rheumatoid arthritis [9], [10], [11], non-Hodgkin’s lymphoma [12], [13] and T- cell lymphoma [14], [15]. In recent phase 2 (CAMMS223) clinical studies, alemtuzumab showed efficacy in the treatment of relapsing-remitting multiple sclerosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Clonal T cells also have been identified in other B-cell malignancies. 20,21 In our study, we have defined a distinct cytotoxic CD8+CD57+ clonal T-cell expansion in the bone marrow occurring in the setting following autologous transplant. The phenotype of this population is strikingly similar to the population described in the peripheral blood of MGUS and myeloma patients.…”
Section: Discussionmentioning
confidence: 98%